Some contributions of hydroelectric power plants to the energy transition and to mitigating Climate Change (Revista Cientifica Ingenio Magno, 2026)
Hydroelectric power is the main source of renewable energy in Colombia, although debates arise regarding its socio-environmental and territorial impacts. However, hydroelectric power is crucial to the country's sustainable energy transition due to its clean and flexible nature. The objective of this reflective article was to analyze the contribution of hydroelectric plants such as Hidroituango, Hidrosogamoso, Chivor, Urrá, and Betania, among others, to the energy transition and climate change mitigation. Environmental, social, economic, and governance dimensions were considered. The methodology involved a document review and comparative analysis of recent research. Fifty-three documents, mostly from Scopus, SciELO, and institutional reports, and to a lesser extent from RedALyC and Latindex, were analyzed in depth. The results showed that hydroelectric power contributes to the stability of the energy system, reduces greenhouse gas emissions, promotes reforestation of watersheds, improves biodiversity, and lessens the impact on communities. Furthermore, they promote tourism, social, and economic development in the regions. Therefore, hydroelectric plants are considered sources of clean, flexible, and low-cost energy compared to fossil fuels. However, the energy transition can be complemented by solar and wind power. It was concluded that hydroelectric plants are strategic as long as their development incorporates mitigation measures, participatory governance, and just transition criteria.
Keywords: Global warming, Climate Change, Clean and flexible energy, Hydroelectric Power, Energy Transition.